ANALYZING THE INFLUENCE OF WORK-FAMILY CONFLICTS AND WORK-LIFE BALANCE TOWARDS EMPLOYEE JOB PERFORMANCE OF DUAL-CAREER COUPLES Case Study: PT Mitra Adiperkasa Fashion Division (MAP Fashion) - Arnesta, Mutiara; Arquisola, Maria Jacinta (President University, 2024)
Nowadays, the manpower contributions in the workforce not only come from male resources, female resources also actively give their contribution to the company, which in this case, in retail industry. This situation creates the opportunity in family household to have both adults have the responsibilities to work and do the household, or having a dual-career couple situation in the household. Which if not managed well, can cause work-family conflict that might affect their job performance at work. This research aims to analyze the influence of work-family conflicts and work-life balance towards employee job performance of dual-career couples in MAP Fashion. In this research, the work-family conflict is divided into three variables based on their factor namely, time-based conflict, strain-based conflict, and behavior-based conflict. This research used quantitative method which 154 employees in MAP Fashion who have working spouse or being in the dual-career couples’ situation are taken as samples. The data were collected using online questionnaires survey with Likert Scale which processed with SPSS. The result of this research shows that time-based conflict and strain-based conflict have significant negative influence towards job performance, and work-life balance have significant positive influence towards job performance of dual-career couple in MAP Fashion.